Rbm24a Is Necessary for Hair Cell Development Through Regulating mRNA Stability in Zebrafish - Zhang, Yan; Wang, Yanfei; Yao, Xuebo; Wang, Changquan; Chen, Fangyi; Liu, Dong; Shao, Ming; Xu, Zhigang (Frontiers in Cell and Developmental Biology, 2020)
Hair cells in the inner ear and lateral lines are mechanosensitive receptor cells whose development and function are tightly regulated. Several transcription factors as well as splicing factors have been identified to play important roles in hair cell development, whereas the role of RNA stability in this process is poorly understood. In the present work, we report that RNA-binding motif protein 24a (Rbm24a) is indispensable for hair cell development in zebrafish. Rbm24a expression is detected in the inner ear as well as lateral line neuromasts. Albeit rbm24a deficient zebrafish do not survive beyond 9 days post fertilization (dpf) due to effects outside of the inner ear, rbm24a deficiency does not affect the early development of inner ear except for delayed otolith formation and semicircular canal fusion. However, hair cell development is severely affected and hair bundle is disorganized in rbm24a mutants. As a result, the auditory and vestibular function of rbm24a mutants are compromised. RNAseq analyses identified several Rbm24a-target mRNAs that are directly bound by Rbm24a and are dysregulated in rbm24a mutants. Among the identified Rbm24a-target genes, lrrc23, dfna5b, and smpx are particularly interesting as their dysregulation might contribute to the inner ear phenotypes in rbm24a mutants. In conclusion, our data suggest that Rbm24a affects hair cell development in zebrafish through regulating mRNA stability.